(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
This article can be support at your lessons how to teach and improve quality of lesson. An incredible way to help bring language immersion both to your classroom and Oto your students outside of school is with FluentU‗s online immersion program. FluentU provides a curated library of real-world video content—including movie trailers, music videos, news and inspiring talks—at levels from complete beginner to native.